The independent and combined associations between the intake of ultra-processed foods, sedentary behavior, and depressive symptoms in young adults - Ren, Jiajia; Zhou, Lei; Li, Yize; Zhang, Shuo; Xu, Xiaoyu; Chi, Xinli; Xie, Hong (Frontiers in Nutrition, 2025)
BackgroundUltra-processed food (UPF) intake and sedentary behavior (SB) are recognized as significant contributors to depressive symptoms. However, the joint effects of these two factors on depressive symptoms remain insufficiently explored. This study aimed to investigate the independent and combined associations of UPF intake and SB with depressive symptoms in a young population.MethodsCross-sectional analyses were conducted using baseline survey data from the Shenzhen Youth Health Cohort. UPF intake, SB, and depressive symptoms were self-reported via questionnaires. Multifactorial logistic regression models were employed to assess the independent and joint associations between UPF intake, SB, and depressive symptoms.ResultsA total of 1,461 participants were included, with 610 (41.8%) reporting depressive symptoms and 851 (58.2%) without. Compared with the group with the lowest UPF supply ratio (Q1), the risk of depressive symptoms was significantly higher in the third (Q3) and fourth (Q4) quartiles, with odds ratios (95% CI) of 1.60 (1.16–2.21) and 2.05 (1.48–2.85), respectively. Similarly, individuals with SB exceeding 8 h per day had a significantly increased risk of depressive symptoms compared to those with SB of less than 4 h per day (OR = 1.75, 95% CI: 1.25–2.44). In the combined analysis, participants with high UPF intake and sedentary time ≥6 h per day exhibited the highest risk of depressive symptoms compared to those with low UPF intake and sedentary time <6 h per day (OR = 2.31, 95% CI: 1.62–3.31).ConclusionHigher intake of UPF and increased SB were significantly associated with depressive symptoms in the young population. Additionally, the combination of high UPF intake and sedentary time exceeding 6 h per day was associated with a further heightened risk of depressive symptoms.